До модернізації об'ємних гідроприводів колісної землерийної машини на базі тракторів ХТЗ - Аврунін, Григорій Аврамович; Ребров, Олексій Юрійович; Пімонов, Ігор Георгійович; Щербак, Олег Виталійович; Мороз, Ірина Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2022)
Проведені дослідження навантажувальних характеристик землерийних машин типу ПЗМ-2(3) та оцінка можливості заміни на об'ємний гідропривід обертання ланцюгового робочого органу та роторного метальника відсипаного ґрунту з підбором гідромоторів та насосів. Встановлено, що для об'ємного гідропривода ланцюгового робочого органу землерийної траншейної машини можуть бути застосовані високомоментні радіальнопоршневі гідромотори з робочим об'ємом 1800...2500 см³ або аксіальнопоршневі гідромотори з планетарними редукторами, для роторного метальника героторні гідромотори з робочим об'ємом 200 см³.

The purpose of the article is to scientifically search for the possibility of replacing mechanical drives of a chain working body and a rotary soil thrower of an earth-moving trenching machine with a hydraulic fluid power in order to increase reliability and effective protection against overloads. Studies have been carried out on the load characteristics of earth-moving machines of the PZM-2 (3) type and an assessment of the possibility of replacing the rotation of the chain working body and the rotary thrower of the dumped soil with the selection of hydraulic motors and pumps for a hydraulic fluid power. Hydraulic actuators must provide operation during the starting mode, minimal power loss during idling and effective protection in the event of a sudden stop of the hydraulic motors due to overloads. As a result of the calculations, it was found that for the hydraulic fluid power of the chain working body earthmoving trencher, high-torque low-speed radial piston hydraulic motors of single or multiple action with a working volume of 1800...2500 cm³, as well as high-speed axial piston hydraulic motors with planetary gearboxes, for a rotary thrower of dumped soil, gerotor hydraulic motors with a working volume of about 200 cm³. The hydraulic motors required by the working volume are mass-produced by a number of foreign companies. To supply the working fluid to the hydraulic motors, axial piston tandem pumps with adjustable displacement, which are produced by the Hydrosila plant, are recommended. The results of the research can be used in the development of a new generation of earth-moving trenching machines when replacing the mechanical drive of the chain working body and the thrower of the dump soil with a hydraulic fluid power.
To the modernization of hydraulic fluid power of wheel earth machine based on HTZ tractors
Keywords: землерийна траншейна машина; робочі органи; об'ємний гідропривід; гідромотор; насос; потужність; крутний момент; earth-moving trench machine; working bodies; hydraulic fluid power; hydraulic motor; pump; power; torque